Agricultural growth, climate resilience, and food security in the Philippines: Subnational impacts of selected investment strategies and policies - Thomas, Timothy S.; Pradesha, Angga; Perez, Nicostrato (International Food Policy Research Institute, 2016)
THE FREQUENCY AND INTENSITY OF TROPICAL CYCLONES IN THE PHILIPPINES HAVE INCREASED IN RECENT years, with detrimental effects for the economy, socioeconomic welfare, and food security. An archipelago known for its climatic and ecological diversity, the Philippines is strongly affected by the adverse impacts of climate change, especially in the agricultural sector. Yet, apart from extreme events, it remains to be seen whether the climate impact will be unequivocally negative, or whether, on balance, some parts of the country may experience gains. An enhanced understanding of how these dynamics will affect the country’s major crops—rice, maize, sugarcane, coconuts, and bananas—is intended to assist Philippine communities in preparing for and adapting to these changes effectively and to assist donors and policy makers in helping them.